Peningkatan Pengetahuan Tentang Metode Pengujian Kekuatan Beton untuk Program Pemeliharaan Gedung - Erna Septiandini; Rosmawita Saleh; Irika Widiasanti; Nadia Fanny Renita (Jurnal Syntax Transformation, 2021)
The cooperation of the college with SMK in accordance with the mandate of Presidential Decree No. 9 of 2016, through increasing aspects of knowledge about the method of testing the strength of concrete structures for building maintenance programs in accordance with Permen PU No: 24 / PRT / M / 2008 for vocational students in Bekasi through webinars. The number of participants who participated in activities from 5 vocational schools in Jakarta and Bekasi as many as 67 participants held on September 12, 2020. Benefits and impacts of activities: (1) measurable of the activity evaluation instrument with pre-test and post-test question instruments will improve aspects of participants' knowledge; (2) benefits to the organizer as an educational institution are obliged to prepare qualified community members and the function of education as a transfer of knowledge; (3) Added value obtained to develop effective methods again. The evaluation results of 61 respondents showed: (1) there was an increase in vocational students' knowledge about regulation in the construction industry which was at 24% - 32% or increased to 15 to 20 people from previously who knew only in the range of 24 - 30 people; and (2) Increase the knowledge aspect for the method of testing the strength of concrete structures in accordance with SNI 2847:2013 for building maintenance programs increased between 10% to 17% or the addition of 6 - 10 people